Gender, rural youth and structural transformation: Evidence to inform innovative youth programming - Doss, Cheryl; Heckert, Jessica; Myers, Emily; Pereira, Audrey; Quisumbing, Agnes R. (International Fund for Agricultural Development, 2019)
The transition to adulthood is marked by interrelated changes in the areas of education, employment and family formation. Using frameworks on gendered transitions to adulthood and links between assets and livelihoods, we analyse nationally representative, sex-disaggregated data from 42 countries to characterize rural youths’ transition to adulthood by gender and according to a four-category typology of low and high levels of structural and rural transformation. Overall, we find that young women and men experience the transition to adulthood differently according to the structural and rural transformation classification of the countries where they live. Across all structural and rural transformation categories, young women are more likely to be married and living with their spouses or in-laws, less likely to be in school or employed, and less likely to own land solely. Gender gaps in secondary school education favour young women only in countries with higher levels of structural and rural transformation, and favour young men in the other three categories. Moreover, a larger proportion of young women than young men are not in education, employment, or training (NEET), but many NEET youth, especially young women, have transitioned into domestic and reproductive roles (i.e. are more likely to be married and/or have children.) Additionally, we review impact evaluations of interventions targeting youth. We find limited evidence on the gendered impacts of such programmes, and these programmes seldom consider how constraints differ for young men and young women. Addressing gaps in programmes and building an evidence base on the gendered impact of interventions can provide insights into how gender roles can simultaneously limit options and offer opportunities to young rural women and men in the context of structural and rural transformation.